Noninvasive quantification of intracellular sodium in human brain using ultrahigh–field MRI. (20th June 2012) - Fleysher, Lazar; Oesingmann, Niels; Brown, Ryan; Sodickson, Daniel K.; Wiggins, Graham C.; Inglese, Matilde
<x xml:space="preserve">Abstract</x> In vivo sodium magnetic resonance imaging (MRI) measures tissue sodium content in living human brain but current methods do not allow noninvasive quantitative assessment of intracellular sodium concentration (ISC) – the most useful marker of tissue viability. In this study, we report the first noninvasive quantitative in vivo measurement of ISC and intracellular sodium volume fraction (ISVF) in healthy human brain, made possible by measuring tissue sodium concentration (TSC) and intracellular sodium molar fraction (ISMF) at ultra‐high field MRI. The method uses single–quantum (SQ) and triple–quantum filtered (TQF) imaging at 7 Tesla to separate intra‐ and extracellular sodium signals and provide quantification of ISMF, ISC and ISVF. This novel method allows noninvasive quantitative measurement of ISC and ISVF, opening many possibilities for structural and functional metabolic studies in healthy and diseased brains. Copyright © 2012 John Wiley & Sons, Ltd.